2012
DOI: 10.3402/ljm.v7i0.19796
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac surgical procedures for the coronary sequelae of Kawasaki disease

Abstract: ObjectivesThe aim of this article is to make an evaluation on the clinical features of patients with Kawasaki disease who require a cardiac surgical procedure including coronary artery bypass grafting, coronary arterial aneurysmorrhaphy or heart transplantation.MethodsEnglish literature of Kawasaki disease for cardiac surgery (1990–2011) was retrieved in the Pubmed database. The clinical features of the patient setting from the representative articles were collected and analyzed.ResultsPatients with Kawasaki d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…The age of onset of KD is small, and cardiac surgery should be performed at an early stage. It has been reported that the average time interval between age of onset and surgical treatment is 9.5 ± 9.4 years[ 21 ]. Anastomosis of the internal mammary artery with LAD is the most common bypass graft approach for CABG.…”
Section: Discussionmentioning
confidence: 99%
“…The age of onset of KD is small, and cardiac surgery should be performed at an early stage. It has been reported that the average time interval between age of onset and surgical treatment is 9.5 ± 9.4 years[ 21 ]. Anastomosis of the internal mammary artery with LAD is the most common bypass graft approach for CABG.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical intervention for giant CAA appears to be the treatment of choice in the reported literature. [ 19 ] Resection of coronary artery aneurysm with CABG is the most frequently chosen treatment modality for giant CAA. [ 20 ] Covered stents were also reported to treat giant CAA.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately half of coronary artery aneurysms resolve within 1-2 years (Bartoloni et al, 2002), but stenosis of the affected vessel might develop with healing (Mueller et al, 2009). Kawasaki patients with coronary aneurysm and/or calcification/thrombus requires coronary artery bypass at a very young age (Yuan, 2012b).…”
Section: Kawasaki Diseasementioning
confidence: 99%